MEMBANGUN KESADARAN ETIKA ONLINE DAN KEMAMPUAN MEMILAH INFORMASI SISWA DESA MEKARJAYA - Purnamasari, Ismi; Ikhsanul Mubarok, Gian; Sari, Wanda; Praharja, Yoga; Sani Febriansyah, Arif; Nasihin, Muhammad; Purnama Yusup, Cahya; Akmal, M; Satia Permana, Dimas; Kirani, Garnis; Puspa Dewi, Erika; Yasin, Yasin; M kustiana, Ruli; Affan Al Sidqi, Muhammad; Rani Rosalba Humaira, Asma; Ajis, Alus; Maulana, Haris; Yulianti Nafisa, Delia; Yassin Al Fadhilah, Muhamad; Supriadi, Ari (Jurnal PkM MIFTEK, 2025)
Awareness of online/digital ethics and the ability to sort information are very important for everyone to have. We have analyzed this awareness and ability in Mekarjaya Village, a village located in Bayongbong District, Garut. With the majority of the population working as farmers and farm labourers, digital literacy is an important aspect in efforts to develop the potential of society in the ever-evolving digital era. Students in Mekarjaya Village are also increasingly connected online, but they are often faced with limited internet access and a lack of awareness about online ethics. This study aims to understand the importance of building online ethical awareness and the ability to sort information among students in Mekarjaya Village. To achieve this goal, a digital literacy program and digital ethics briefing have been implemented in one of the junior high schools in Mekarjaya village, namely Persis Al-Manar Middle School. The methods used include lectures, discussions, and questions and answers. The results showed an increase in students' understanding of digital literacy and digital ethics, as well as improvements in their online behavior. This research provides important insights into the challenges and potentials of digital literacy in rural areas and offers solutions in the form of relevant educational programs.